2022
DOI: 10.21037/tcr-21-2635
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of desflurane and propofol in the speed and the quality of emergence from anesthesia in patients undergoing lung cancer surgery—a prospective, randomized study

Abstract: Background Anesthesia with desflurane or propofol enables rapid emergence. In patients undergoing lung cancer surgery, however, the speed of emergence from desflurane, but not from propofol, may be affected by the deteriorated postoperative respiratory function. We prospectively compared the speed and quality of emergence between desflurane and propofol. Methods We conducted a parallel study. Eighty patients scheduled for lung cancer surgery were randomly allocated to D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Previous study indicated that as an anesthesia adjunct, dexmedetomidine prolonged anesthesia emergence [ 41 ], but this study indicated that the emergence time of dexmedetomidine-led anesthesia was 4.8 min, which was shorter than short-duration anesthetic propofol (emergence time, 5.9 min) and desflurane (emergence time, 5.7 min) [ 42 ]. We provided intensive anesthesia depth monitoring during maintenance and no intraoperative awareness events occurred, but based on Wilson confidence interval calculation, the upper confidence limit of occurrence rate of intraoperative awareness was 3.27% (sample size = 30).…”
Section: Discussionmentioning
confidence: 94%
“…Previous study indicated that as an anesthesia adjunct, dexmedetomidine prolonged anesthesia emergence [ 41 ], but this study indicated that the emergence time of dexmedetomidine-led anesthesia was 4.8 min, which was shorter than short-duration anesthetic propofol (emergence time, 5.9 min) and desflurane (emergence time, 5.7 min) [ 42 ]. We provided intensive anesthesia depth monitoring during maintenance and no intraoperative awareness events occurred, but based on Wilson confidence interval calculation, the upper confidence limit of occurrence rate of intraoperative awareness was 3.27% (sample size = 30).…”
Section: Discussionmentioning
confidence: 94%